THE PROCEDURE FOR LIQUIDATION OF COMPANIES - Soghomonyan, Ashkhen (State and Law, 2021)
The paper discusses the established legal liquidation procedure for commercial organizations. Basing on the analysis of the legal regulation of liquidation procedure, the author lists its basic shortcomings and makes suggestions to improve certain legal provisions.
Keywords: liquidation procedure; stages; deadlines; liquidation balance sheet; interim liquidation balance sheet; liquidation commission; protection of creditors' rights; distribution of property